The trouble with personhood and person‐centred care. (13th April 2022) - Tieu, Matthew; Mudd, Alexandra; Conroy, Tiffany; Pinero de Plaza, Alejandra; Kitson, Alison
Abstract: The phrase 'person‐centred care' (PCC) reminds us that the fundamental philosophical goal of caring for people is to uphold or promote their personhood. However, such an idea has translated into promoting individualist notions of autonomy, empowerment and personal responsibility in the context of consumerism and neoliberalism, which is problematic both conceptually and practically. From a conceptual standpoint, it ignores the fact that humans are social, historical and biographical beings, and instead assumes an essentialist or idealized concept of personhood in which a person is viewed as an individual static object. From a practical standpoint, the application of such a concept of personhood can lead to neglect of a person's fundamental care needs and exacerbate the problems of social inequity, in particular for older people and people with dementia. Therefore, we argue that our understanding of PCC must instead be based on a dynamic concept of personhood that integrates the relevant social, relational, temporal and biographical dimensions. We propose that the correct concept of personhood in PCC is one in which persons are understood as socially embedded, relational and temporally extended subjects rather than merely individual, autonomous, asocial and atemporal objects. We then present a reconceptualization of the fundamental philosophical goal of PCC as promoting selfhood rather than personhood. Such a reconceptualization avoids the problems that beset the concept of personhood and its application in PCC, while also providing a philosophical foundation for the growing body of empirical literature that emphasizes the psychosocial, relational, subjective and biographical dimensions of PCC.